Large-scale synthesis of polydimethylsiloxane as vitreous replacement applications - Ajrina Nur Shabrina; Diba Grace Auliya; Risdiana; Lusi Safriani (Designed Monomers and Polymers)
Polydimethylsiloxane (PDMS) is a polymer that can be used as a vitreous substitute. To fulfill the need for PDMS on a large scale, synthesis of PDMS in a large number is also needed. Therefore, intensive research is needed to produce PDMS in large quantities. This study reported that the result of the synthesis of PDMS on a scale three and five times larger than the lab-scale using a ring-opening polymerization method with octamethylcyclotetrasiloxane (D4) as a monomer and hexamethyldisiloxane as a chain terminator by increasing the volume of raw materials and reactors. The viscosity of PDMS obtained is in the ranges of 1000–3700 mPa.s for lab-scale, 1130–3590 mPa.s for three times scale-up, and 1270–4320 for five times scale-up. The obtained refractive index ranges from 1.3982 to 1.4008 and the surface tension ranges from 20 to 21 mN/m. From FTIR measurements, the synthesized PDMS from lab-scale and scale-up had structural and functional groups similar to commercial PDMS, showing that PDMS has been successfully synthesized.